The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.28982/josam.755795
|View full text |Cite
|
Sign up to set email alerts
|

Working conditions and burnout syndrome in private bank branch employees in Ankara, Turkey

Abstract: Background/Aim: Burnout is a syndrome of physical exhaustion, prolonged fatigue, and helplessness reflected by negative attitudes on work, life, and other people around. The aim of this study is to investigate the relationship between burnout and working conditions in the banking sector, which has intense emotional demands. Methods: The research group consisted of 1183 individuals working in 138 different branches. A data form questioning the working conditions and sociodemographic characteristics of the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…According to Amigo et al (2014), burnout may be caused by employees' frequent contact with demanding clients. Employees who dealt with too many clients in a day reported higher levels of burnout, according to the findings of a study conducted in a private bank branch in Ankara, Turkey (Koyuncu et al, 2021). Similar findings were obtained in a study that included 259 employees from five banks in Zimbabwe, in which employees felt emotionally exhausted due to constant interaction with clients and the need to always maintain formal communication, without expressing their emotions (Ndengu & Leka, 2022).…”
Section: Source: the Authorssupporting
confidence: 70%
See 1 more Smart Citation
“…According to Amigo et al (2014), burnout may be caused by employees' frequent contact with demanding clients. Employees who dealt with too many clients in a day reported higher levels of burnout, according to the findings of a study conducted in a private bank branch in Ankara, Turkey (Koyuncu et al, 2021). Similar findings were obtained in a study that included 259 employees from five banks in Zimbabwe, in which employees felt emotionally exhausted due to constant interaction with clients and the need to always maintain formal communication, without expressing their emotions (Ndengu & Leka, 2022).…”
Section: Source: the Authorssupporting
confidence: 70%
“…One of the major issues confronting employees in the banking sector is occupational burnout (Khalid et al, 2020;Tafi et al, 2022;Tehrani et al, 2021). Numerous studies have shown that employees in the banking sector are constantly under pressure due to heavy workload, rapid and intense technological changes, fierce competition, and responsibility for high financial results (Al-Kahtani & Allam, 2013;Awwad et al, 2022;Hashemnia et al, 2014;Iakymenko et al, 2015;Khattak et al, 2011;Koyuncu et al, 2021;Lubbadeh, 2021). The International Labor Organization identified a number of concerns that workers in the banking sector must cope with, including increased deadline pressure, ergonomic issues, an increase in violence, challenging and demanding clients (Giga & Hoel, 2003).…”
Section: Occupational Burnout In Banking Sectormentioning
confidence: 99%